2009
DOI: 10.1038/nature07612
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/calmodulin regulates salicylic-acid-mediated plant immunity

Abstract: Intracellular calcium transients during plant-pathogen interactions are necessary early events leading to local and systemic acquired resistance. Salicylic acid, a critical messenger, is also required for both of these responses, but whether and how salicylic acid level is regulated by Ca(2+) signalling during plant-pathogen interaction is unclear. Here we report a mechanism connecting Ca(2+) signal to salicylic-acid-mediated immune response through calmodulin, AtSR1 (also known as CAMTA3), a Ca(2+)/calmodulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
572
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 486 publications
(608 citation statements)
references
References 40 publications
23
572
3
1
Order By: Relevance
“…For example, altered Ca 2ϩ /CaM binding to DWF1 documented the possibility of producing size-engineered plants (6), although altered Ca 2ϩ and Ca 2ϩ /CaM binding to chimeric calcium/calmodulin-dependent protein kinase produces spon- taneous nodulation (7). Recently, we characterized the CaMbinding transcription factor AtSR1, which doses the salicylic acid level and regulates plant immunity (41). Redesigning CRLK1 orthologs in crop plants by manipulating their CaMbinding sites will help to enhance their ability to respond to the stress signal and to engineer stress-tolerant crops.…”
Section: Discussionmentioning
confidence: 99%
“…For example, altered Ca 2ϩ /CaM binding to DWF1 documented the possibility of producing size-engineered plants (6), although altered Ca 2ϩ and Ca 2ϩ /CaM binding to chimeric calcium/calmodulin-dependent protein kinase produces spon- taneous nodulation (7). Recently, we characterized the CaMbinding transcription factor AtSR1, which doses the salicylic acid level and regulates plant immunity (41). Redesigning CRLK1 orthologs in crop plants by manipulating their CaMbinding sites will help to enhance their ability to respond to the stress signal and to engineer stress-tolerant crops.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear what other signals induce the CAM box, although a role for the CAMTA transcription factors that bind this motif has also been shown in response to pathogens and auxin (Galon et al, 2008;Du et al, 2009;Galon et al, 2010b), which also provoke elevations in [Ca 2+ ] c (Felle, 1988;Knight et al, 1996;Grant et al, 2000). The CRT element is also induced in response to drought (Liu et al, 1998), and the ABRE is induced in response to ABA and drought (Hobo et al, 1999), which both induce [Ca 2+ ] c (McAinsh et al, 1990;Knight et al, 1996;Knight et al, 1997).…”
Section: Identification Of Four Promoter Motifs That Are Overrepresenmentioning
confidence: 99%
“…The expression of specific stress-responsive genes has been demonstrated to be calciumregulated, for example, in response to cold (Knight et al, 1996;Knight et al, 1997;Tä htiharju et al, 1997;Galon et al, 2010a). The protein intermediates brokering calcium signals to regulate gene expression have also, in some cases, been identified, for example calmodulins (CaMs) (Takahashi et al, 2011), CaM-like proteins (Chiasson et al, 2005;Magnan et al, 2008;Xu et al, 2011), calcium-dependent protein kinases (CPKs) (Boudsocq et al, 2010;Coca and Segundo, 2010), CIPK/CBLs (Albrecht et al, 2003;Weinl and Kudla, 2009), and even transcription factors, such as CaM-binding transcription activators (CAMTAs) (Galon et al, 2008;Doherty et al, 2009;Du et al, 2009;Galon et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated Ca 2+ influx and transients followed by pathogen recognition comprises a major part of disease signal transduction (Du et al, 2009). One of the major responses by infectioninduced cytosolic Ca 2+ influx is the generation of hypersensitive response (HR) and ROS production.…”
Section: Calcium Signal Regulation At the Point Of Aba And Disease Simentioning
confidence: 99%
“…Moreover pharmacological experiments with Calmodulin (CaM) antagonist and the calmodulin-like24-4 (cml24-4) mutant demonstrated that Ca 2+ influx mediates generation of Nitric oxide (NO) signals through activation of CaM or CML (Ma et al, 2008). For the decoding of pathogen-induced Ca 2+ signature, AtSR1 also known as Ca 2+ /calmodulin-binding transcription factor3 (CAMTA3) acts as a negative regulator of SA signaling-mediated HRs by binding to the promoter of the EDS1 gene (Du et al, 2009). In addition, CDPKs could also play a role as positive regulators in disease responses by transferring Ca 2+ signals to downstream target elements.…”
Section: Calcium Signal Regulation At the Point Of Aba And Disease Simentioning
confidence: 99%